Relevance of the Mention of Antioxidant Properties in Yogurt Labels: In Vitro Evaluation and Chromatographic Analysis - Eliana Pereira; Lillian Barros; Isabel C. F. R. Ferreira (MDPI AG, 2013)
The purpose of the inclusion of fruit (natural additives) in yogurt aims to increase its antioxidant activity and functionality. Herein, a comparative study of the antioxidant potential of yogurts with pieces of various fruits was performed, including yogurts with mention of antioxidant properties in the label. Free radicals scavenging activity, reducing power and inhibition of lipid peroxidation were evaluated by in vitro assays, as were the contents in antioxidants such as phenolics, flavonoids, sugars and tocopherols. After analyzing thirteen yogurts containing fruit pieces and a natural one (control), the most interesting were yogurts with pieces of berries (for phenolics, flavonoids and 2,2-dipheny-1-picrylhydrazyl (DPPH) scavenging activity), pineapple (for reducing power), blackberry (for β-carotene bleaching inhibition), blackberry "antioxidant" (for tocopherols) and cherry (for sugars). The mention of "antioxidant" in the label was relevant for tocopherols, sugars, DPPH scavenging activity and reducing power. No synergisms were observed in yogurts prepared with pieces of different fruits. Nevertheless, the addition of fruit pieces to yogurt was favorable for antioxidant content, increasing the protection of the consumer against diseases related to oxidative stress.